Strategic control of acute diarrhea of newborn calves - Chotiah, Siti (Indonesian Journal of Animal and Veterinary Sciences, 2012)
Economic performance of beef cattle operations can be severely hampered by acute calfhood diarrhea. Accordingly, a study was conducted at Bbalitvet to identify the causal agents, reduce clinical incidence, and increase body weight gain of newborn calves. One potential control is application of suitable vaccines to pregnant cows. The study was begun by identifying cases of diarrhea followed by isolation and identification of the causal agents in 12 beef cattle farms in West Java. A field trial was then designed for controlling calf diarrhea in such farms. Inactive vaccines Ecoli-Closvak polivalen were administered to pregnant cows to increase specific resistance of the newborn calves. At 2 months prepartum, 12 pregnant cows were assigned either to a vaccination or a placebo group, with a booster vaccination 3 weeks prior to parturition. Strict hygenic management was provided to both groups, and all calves were provided adequately with colostrum.Â  Subjects were observed for 5 months, starting from the time of initial vaccination until the calves were 3 months of age. In the initial farm surveys, entero-pathogenic bacteria such as Escherichia coli serotype K99 and Clostridium perfringens type A and C were isolated and identified in fecal samples from 4 beef cattle farms in 3 districts (Garut, Tasikmalaya, Ciamis) and 2 beef cattle farms in 2 districts (Tasikmalaya and Ciamis) of West Java. In the vaccination trial, good immune responses to E. coli and C. perfringens alpha toxin measured by ELISA were observed. Application of effective control of calf diarrhea including vaccination and good livestock management showed good results. No death or signs of diarrhea were found in the new born calves up to 3 months of age. The rate of body weight gain was significantly higher in calves of vaccinated dams than in calves of non-vaccinated dams. Key Words: Strategic control, Calf diarrhea